Asas-Asas Perjanjian dalam Hukum Perjanjian Syariah - Miftahus Salam (Asy-Syari’ah : Jurnal Hukum Islam, 2017)
The term of “akad” has an important meaning in the life of the community. Akad is “the foundation of many of our daily activities.” Through Akad a man’s is united with a woman in a common life, and through Akad also various business activities and our business can be run. Akad facilitates each person in meeting his needs and interests that he can not fulfill without the help and services of others. It is therefore justifiable to say that the covenant is a social means found by human civilization to support its life as a social being. In Islamic law there are principles of agreement underlying its enforcement and implementation. In this article there are nine principles of agreement (Akad) that can be used as a basis for thinking and transacting in Islamic legal agreements. The principles of the Akad are, the principle of the mother, the principle of freedom of conscience, the principle of consensualism, the principle of the promise is binding, the principle of balance, the principle of benefit, the principle of trust, and the principle of justice, and the principle of personnel.